Determining The Pattern of Pesticide Residue Contamination and The Improvement of Production, Quality, and Milk Safety of Dairy Cattle with Probiotic-based Lignochloritic Bacteria - Prihartini, Indah (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Agricultural waste is a substitute for forage as the main feed of dairy cattle, especially duringthe dry season. The quality of agricultural waste in Indonesia is very low, with the high content oflignocelluloses which limits digestibility of feed. On the other hand, bioaccumulation of pesticides inplants that occurs during lignifications process caused the highest number of residues found in hayand straw that is lower in security as animal feed. The research objective was to determine thepattern of pesticide residue contamination in dairy products and dairy feed, as well as theimprovements to the production, quality, and safety of dairy product. The result showed that forageproducts, concentrates, and milk were detected to contain 6 harmful organochlorin pesticideresidues, namely lindane, heptachlor, eldrin, diendrin, aldrin and DDT. The number of aldrin, DDT,and dileldrin in diendrin milk was as high as between 5.76 to 19.2 ppb. The mechanism ofcontamination patterns of each pesticide differs, and sources of contamination derived fromconcentrates, forage, and other resources such as drinking water. The application of probiotic-basedlignochloritic bacteria 1% of the total concentrate feed has increased milk production 30-50% ofcontrol, increasing the average fat content of 4.0% and lower organochlorin residues in milkbetween 60-100%.Key Words: Probiotic, Lignochloritic, Pesticide, Residue